Patterns and Scales in Gastrointestinal Microbial Ecology - Camp, J. Gray (Gastroenterology, 2009)
The body surfaces of humans and other animals are colonized at birth by microorganisms. The majority of microbial residents on the human body exist within gastrointestinal (GI) tract communities, where they contribute to many aspects of host biology and pathobiology. Recent technological advances have expanded our ability to perceive the membership and physiologic traits of microbial communities along the GI tract. To translate this information into a mechanistic and practical understanding of host-microbe and microbe-microbe relationships, it is necessary to recast our conceptualization of the GI tract and its resident microbial communities in ecological terms. This review depicts GI microbial ecology in the context of 2 fundamental ecological concepts: (1) the patterns of biodiversity within the GI tract and (2) the scales of time, space, and environment within which we perceive those patterns. We show how this conceptual framework can be used to integrate our existing knowledge and identify important open questions in GI microbial ecology.